Computer-Mediated Argumentation in Higher Education: Developing Discussion Skills via Roles - Pilkington, Rachel (Proceedings of the International Conference on Networked Learning, 2002)
Many authors advocate providing opportunities for critical discussion to develop students’ abilities to reason in a specialist subject. Computer Mediated Communication (CMC) offers some distinct advantages as well as disadvantages for debate. Research in analyzing CMC dialogue is revealing that effective discussions involve different kinds of role-taking including community building and management roles as well as argumentation roles. Our hypothesis was that making post-graduate students aware of all three kinds of role would lead to wider independent adoption of these roles by students. Based on student perceptions and further analysis by the researcher some preliminary results are presented.